Trigger tools in healthcare settings: insights from an umbrella review - Mohammed As'ad; Nawarh Faran; Awad Al Omari (BMJ Open Quality, 2025)
Objective This study synthesises the effectiveness and applicability of trigger tools for detecting adverse events (AEs) across various healthcare settings.Design This study used an umbrella review to consolidate findings from existing systematic reviews, assess the quality of evidence and identify gaps in current knowledge.Methods A comprehensive search was conducted across SCOPUS, Web of Science and PubMed, and included systematic reviews and meta-analyses from 2009 to 2024 focusing on trigger tools used in healthcare settings. Data extraction and quality appraisal followed Joanna Briggs Institute guidelines. Narrative synthesis was employed owing to the heterogeneity among studies. Nine systematic reviews were included.Results Nine systematic reviews were analysed. Results showed substantial variation in trigger tool performance. Detection rates ranged from 0.8% to 66% across healthcare settings and populations. Preventability rates varied widely from 7% to 94.4%. Automated detection methods demonstrated inconsistent results with AE prevalence, ranging from 0.1% to 29.2%. The studies within the reviews exhibited significant variability in the types of trigger tools analysed and the methodologies used, affecting detection outcomes. The quality of the included studies varied, with inconsistent definitions of AEs and differences in study design limiting the generalisability of the findings.Conclusions Trigger tools vary significantly in effectiveness, influenced by healthcare context and tool design. Automated methods need refinement. Standardised methodologies and context-specific tools are essential to improve patient safety. Future research should focus on these areas to enhance the accuracy and applicability of trigger tools in different healthcare settings.PROSPERO registration number CRD42024581456.